Evaluating Health and Safety Practices In Sawmills: The Case of Naja David Veneer and Plywood (NDVP) Ltd., Kumasi - Alewabah, Stephen Benyaseh (2011)
A thesis submitted to the Department of Community Health, School of Medical Sciences, College of Health Sciences Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of MSc.degree in Health Services Planning and Management,